2015
DOI: 10.2174/1385272819666150608220335
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of Birch Reduction in Total Synthesis of Natural Products

Abstract: The Birch reduction is unique, in synthetic approaches, due to the adaptable substitution patterns of the substituted cyclohexa-1,4-and 1,3-dienes, particularly enol ethers. Birch reduction as a key and sometimes as the only reduction tool has found several applications in total synthesis of several natural occurring compounds. This name reduction is very important and quite useful for reduction of aromatic and none-aromatic moieties. It is particularly useful in aromatic compounds due to its selectivity of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…We also are kin to update the applications of name reactions in the total synthesis of natural products [118][119][120][121][122][123][124][125][126][127][128] and applications of different synthons, reagents and catalysts in organic synthesis [129][130][131][132][133][134][135] .…”
Section: Introductionmentioning
confidence: 99%
“…We also are kin to update the applications of name reactions in the total synthesis of natural products [118][119][120][121][122][123][124][125][126][127][128] and applications of different synthons, reagents and catalysts in organic synthesis [129][130][131][132][133][134][135] .…”
Section: Introductionmentioning
confidence: 99%
“…Another synthetic strategy to target this skipped diene-motif inside a ring is to use the corresponding aromatic compounds and submit them to dissolved metal (Birch) reduction conditions (Scheme 1,B). [14,15] Unfortunately, this strategy does not yield the desired selectivity as the carboxylate directs the reduction to the ipso position. Recently, Hall and co-workers published a new method for the [2 + 4] cycloaddition of propiolic acid with 1,3-dienes using boron catalysis under very mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our research group showed interest and focused on the applications of name reactions in the total synthesis of natural products . Among them, in 2012 we published a report, covering the applications of SMCR in the total synthesis of natural products in Tetrahedron, which has seemingly attracted much attention of synthetic organic chemists due to numerous citations it has gained till date.…”
Section: Introductionmentioning
confidence: 99%